Poor fen succession over ombrotrophic peat related to late Holocene increased surface wetness in subarctic Quebec, Canada - van Bellen, Simon; Garneau, Michelle; Ali, Adam A.; Lamarre, Alexandre; Robert, Élisabeth C.; Magnan, Gabriel; Asnong, Hans; Pratte, Steve (Journal of Quaternary Science, 2013)
Northern peatlands act as archives of environmental change through their sensitivity to water balance fluctuations, while being significant contributors to global greenhouse gas dynamics. Subarctic fens in northeastern Canada are characterized by a dominance of pools and flarks. We aimed to reconstruct the late-Holocene hydrological conditions of these fens to establish the timing of the initiation of pool and flark formation and possible linkages with climate. Testate amoebae and plant macrofossils from five cores, sampled in three fens, were analyzed to infer water tables with chronologies based on 14C and 210Pb dating. All sites showed presence of relatively dry, ombrotrophic conditions with abundant Picea from 5000 cal a BP, followed by a first shift to wet, poor fen conditions with pool and flark development around 3000 cal a BP and a subsequent wet shift after ~800 cal a BP. These trends coincide with previously observed Neoglacial and Little Ice Age cooler and wetter conditions and therefore climate may well have been a dominant factor in the initiation and development of pools and flarks over the late-Holocene. The effect of anticipated climate change on subarctic peatlands remains unclear, although wetter conditions might enhance pool expansion to the detriment of terrestrial components.